2006
DOI: 10.1016/j.jaap.2005.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Thermogravimetric analysis during the decomposition of cotton fabrics in an inert and air environment

Abstract: The thermal degradation of samples of used cotton fabrics has been investigated using thermogravimetric analysis (TGA) between room temperature and 700 8C. Experiments were carried out with about 5 mg of sample in three different atmospheres: helium, 20% oxygen in helium and 10% oxygen in helium. Three different heating rates were used at each atmosphere condition. A kinetic model for the decomposition of used cotton fabrics explaining the behavior of all the runs performed has been proposed and tested. For th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 24 publications
5
15
0
Order By: Relevance
“…The first exothermic peak began at 180 °C and finished at 350 °C, which was assigned to the carbonization process of the cellulose. The results were in accordance with previously reported values (Wielage et al 1999;Moltó et al 2006). The exothermic peak at 450 °C indicated the phase transformation of TiO2 from the anatase to rutile phase.…”
Section: Xrd Analysis Of the Composite Catalystssupporting
confidence: 92%
“…The first exothermic peak began at 180 °C and finished at 350 °C, which was assigned to the carbonization process of the cellulose. The results were in accordance with previously reported values (Wielage et al 1999;Moltó et al 2006). The exothermic peak at 450 °C indicated the phase transformation of TiO2 from the anatase to rutile phase.…”
Section: Xrd Analysis Of the Composite Catalystssupporting
confidence: 92%
“…Waste lubricant oil was collected from a tank in a local garage: all experiments were done with as-received waste oil (non-filtered) [7,15]. Cotton fabric, a used blue T-shirt made of 100% cotton represented the used cotton fabric source: the T-shirt was cut into small pieces with an average size of 1 by 1 cm [8].…”
Section: Methodsmentioning
confidence: 99%
“…After collecting the exit gas for 5 min, the holder was removed from the furnace. More details regarding the experimental procedure can be found elsewhere [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16].…”
Section: Methodsmentioning
confidence: 99%
“…The second weight-loss stage began at 275 8C and finished at 330 8C, indicating that cellulose began to decompose at 275 8C and the carbonization process finished at 330 8C, which is in accordance with literature reports. [40,41] After the carbonization of the cellulose component, the mass loss continued, and an exothermic peak at 405 8C emerged in the DSC curve, indicating the transformation of the as-deposited amorphous titania to crystalline anatase. [42] Energy-dispersive X-ray (EDX) spectroscopic results showed that titanium, oxygen, and carbon components were observed for the titania-coated, carbon nanofibrous material, in which the carbon component is apparently derived from the pyrolysis of the filter paper (see the Supporting Information, Figure S1).…”
Section: Resultsmentioning
confidence: 99%